Effect of interfacial reaction on the tensile strength of Sn-3.5Ag/Ni-P and Sn-37Pb/Ni-P solder joints - Qi, Guojun (2013)
This work investigates the effect of interfacial reaction on the mechanical strength of two types of solder joints, Sn-3.5Ag/Ni-P and Sn-37Pb/Ni-P. The tensile strength and fracture behavior of the joints under different thermal aging conditions have been studied. It is observed that the tensile strength decreases with increasing aging temperature and duration. Associated with the tensile strength decrease is the transition of failure modes from within the bulk solder in the as-soldered condition toward failures at the interface between the solder and the intermetallic compounds (IMCs). For the same aging treatment, the strength of the Sn-3.5Ag/Ni-P joint degrades faster than that of Sn-37Pb/Ni-P. The difference between the two types of joints can be explained by the difference in their interfacial reaction and growth kinetics. An empirical relation is established between the solder joint strength and the Ni3Sn4 intermetallic compound thickness.